2013
DOI: 10.1111/hepr.12157
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β induces tumor necrosis factor‐α secretion from rat hepatocytes

Abstract: IL-1β-stimulated rat hepatocytes are a newly identified source of TNF-α in the liver. TNF-α mRNA and asRNA are expressed in rats and humans, and the TNF-α asRNA reduces the stability of the TNF-α mRNA. Hepatocytes and TNF-α asRNA may be therapeutic targets to regulate levels of TNF-α mRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…Importantly, treatment of liver with LPS leads to release of proinflammatory cytokines IL1b and TNFa from both nonparenchymal cells and hepatocytes. Stimulation with IL-1b induces TNFa secretion from rat hepatocytes, and stimulation of hepatocytes with either IL-1b or TNFa produces IL-6 secretion (Panesar et al, 1999;Yoshigai et al, 2014). Hence, there are multiple levels of interconnection and amplification that occur rapidly between and among inflammatory cytokines after bacterial sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, treatment of liver with LPS leads to release of proinflammatory cytokines IL1b and TNFa from both nonparenchymal cells and hepatocytes. Stimulation with IL-1b induces TNFa secretion from rat hepatocytes, and stimulation of hepatocytes with either IL-1b or TNFa produces IL-6 secretion (Panesar et al, 1999;Yoshigai et al, 2014). Hence, there are multiple levels of interconnection and amplification that occur rapidly between and among inflammatory cytokines after bacterial sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent investigations have indicated that this is in fact not the case. Hepatocytes mount a robust response to challenge with either LPS or IL-1b to produce key inflammatory cytokines, including IL-6, TNFa, and IL-1b (Liu et al, 2002;Panesar et al, 1999;Spencer et al, 2013;Takano et al, 2012;Yoshigai et al, 2014). It is also now well known that hepatocytes express all the necessary machinery to respond to bacterial sepsis , TABLE 5 Expression level of IL-1b, IL-6, TNFa, and IL1-Ra in wild-type and PXR-KO PCHs PCHs isolated from wild-type (n = 6) or PXR-KO mice (n = 6) were pretreated for 24 hours with either vehicle (0.1% dimethylsulfoxide) or PCN (10 mM).…”
Section: Discussionmentioning
confidence: 99%
“…However, many of the cytokines produced by hepatic immune cells can cause hepatocyte injury, and IL-1β, IL-6 andTNF-α are especially dangerous [2,3]. Furthermore, IL-1β has been reported to induce high levels of TNF-α [4,5] and IL-6 [6] in hepatocytes and osteoblasts, respectively. Because 80% of the liver volume consists of hepatocytes [7], the prevention of hepatocyte injury is an important consideration when designing therapeutic strategies [2].…”
Section: Introductionmentioning
confidence: 99%
“…This method is referred to as natural antisense transcript-targeted regulation (NATRE) technology [22] . In contrast, when sense oligonucleotides corresponding to other mRNAs that are involved in inflammation (e.g., mRNAs encoding TNF-alpha, nuclear factor-kappaB p65 subunit, and several chemokines) were introduced into hepatocytes, their mRNA levels increased (discordant regulation) [23,24] .…”
Section: Inflammation and Infectionmentioning
confidence: 98%
“…Both sense oligodeoxyribonucleotides [11,[21][22][23][24] and antisense oligoribonucleotides (asRNA mimics) [6] have been successfully used to interfere with this interaction. The copy number of an asRNA is generally lower than that of an mRNA, although asRNAs have high specificity to their cognate mRNAs.…”
Section: Regulatory Rna Networkmentioning
confidence: 99%